Socio-economic impact of Blockchain utilization on Digital Certificates - Rahardja, Untung; Aini, Qurotul; Budiarty, Frizca; Yusup, Muhamad; Alwiyah, Alwiyah (APTISI Transactions on Management (ATM), 2021)
This research is an effective digital certificate publishing activity by utilizing blockchain technology. By implementing decentralized systems and cryptography owned by the blockchain, it will potentially enlarge the educational progress space in Indonesia. The weakness of the current running system, lies in the difficulty of identifying the validity of a certificate issued by an educational institution. Therefore, the advantages that blockchain has, able to assist an educational institution, in establishing a widely accessible certification system infrastructure, to support the transparency and accountability of an educational institution, in identifying the validity of the certificate. Blockcert as one of MIT's tools, while acting as a barometer, is used to perform a series of activities in publishing activities and the implementation of official documents that are designed based on a technology commonly referred to as Blockchain. The research conducted will demonstrate that a decentralized consensus will be able to provide good distribution of information that can include all certificate deployment activities